2019
DOI: 10.18245/ijaet.625754
|View full text |Cite
|
Sign up to set email alerts
|

Predicted fuel characteristics of prunus avium seed oil as a candidate for biodiesel production

Abstract: Energy is an indispensable requirement for both developed and developing societies today. However, most of the energy needs are met by fossil fuels, these resources are not renewable. Many countries are evaluating alternative sources to meet energy demand and to sustain development. In this study, oil was obtained by using Prunus avium kernels, also known as Turkish Cherry cultivated from Pozantı which is on the Taurus Mountains. Oil characterization was performed by gas chromatography (GC) and free fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The main fatty acids in Luffa Aegyptiaca seed oil are 43.85% Linoleic acid, 33.00% Oleic acid, 13.79% Palmitic acid and 7.90% Stearic acid by weight, respectively. Due to their large percentage values, linoleic and oleic acids are the principal fatty acids that have an impact on the characteristics of Luffa Aegyptiaca biodiesel [16]. The chromatography spectrum is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main fatty acids in Luffa Aegyptiaca seed oil are 43.85% Linoleic acid, 33.00% Oleic acid, 13.79% Palmitic acid and 7.90% Stearic acid by weight, respectively. Due to their large percentage values, linoleic and oleic acids are the principal fatty acids that have an impact on the characteristics of Luffa Aegyptiaca biodiesel [16]. The chromatography spectrum is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…The oil was characterized using gas chromatography (GC), and the free fatty acids were computed. The anticipated outcomes demonstrated that Prunus avium seed oil is an effective substitute for biodiesel [16].…”
Section: Scientists Evaluated Many Non-edible Oils Such Asmentioning
confidence: 99%
See 1 more Smart Citation
“…The important of knowing fatty acid composition of the feedstock used to produce biodiesel because it was have a significant effect on the quality of the biodiesel product. Biodiesel was typically produced from triglycerides (fats and oils), [11], the composition of these triglycerides, specifically the types of fatty acids they contain, can impact various properties of the biodiesel, including its cetane number, cold flow properties, oxidative stability, and overall performance. The prevoius study of fatty acid component of Pometia pinnata were not found until the present moment, this study then aimed to analyzing the fatty acid of Pometia pinnata with the purpose to make it use as a biodiesel raw material to produce biodiesel.…”
Section: Introductionmentioning
confidence: 99%